Geographic Information System of College at Banyumas Regency Based on Android - Suyudi Suyudi; Ella Laela Sari; Endang Setyawati (INCODING: Journal of Informatics and Computer Science Engineering, 2021)
Banyumas Regency is a student city in Central Java which has 21 tertiary institutions, consisting of state and private tertiary institutions, spread throughout the Banyumas region. With so many PTs available, it is often difficult for prospective students from out of town to get locations, so by building an Android-based Geographic Information System for Banyumas Higher Education Institutions that is built to help and facilitate the community or prospective students. With the prototype method with steps (communication, planning, modeling, prototype formation, and evaluation). The scope of the system includes the GPS assistance facilities. The main menu contained in the application of PTN and PTS about the brief description of information about tertiary institutions, facility menus from the ATM, gas station and hospital sub menus, emergency call menus containing important telephone numbers such as the police and fire department , and help menu how to use the application. Conclusions The study states that HI was accepted, namely "There is a significant time difference in the process of finding the location of tertiary institutions before and after using the Geographic Information System for Higher Education in Banyumas Regency on Android". Then based on the results of product tests that have been done show that the product test value to determine the quality of the system being built is 96.85, the value is greater than the feasibility limit of 75. Thus, the system built is suitable for use by the wider community.